2020
DOI: 10.3390/membranes10110319
|View full text |Cite
|
Sign up to set email alerts
|

Clarification of 1,3-Propanediol Fermentation Broths by Using a Ceramic Fine UF Membrane

Abstract: This work examined the use of a ceramic fine ultrafiltration (UF) membrane for the pre-treatment of 1,3-propanodiol (1,3-PD) fermentation broths. It has been demonstrated that the membrane used provides obtaining a high-quality, sterile permeate, which can be sequentially separated by other processes such as nanofiltration (NF) and membrane distillation (MD). Special attention was paid to the impact of the operational parameters on the membrane performance. The series of UF experiments under transmembrane pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 103 publications
4
18
0
Order By: Relevance
“…Roughly speaking, the membrane efficiency can be increased due to the cake formation, as particles with diameters smaller than the pore size of the membrane are more susceptible to being captured by the cake [ 79 ]. An apparent decrease in the turbidity of permeate samples during the pressure driven separation processes of fermentation broths has also been reported in several previous studies [ 5 , 7 , 72 , 80 ].…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…Roughly speaking, the membrane efficiency can be increased due to the cake formation, as particles with diameters smaller than the pore size of the membrane are more susceptible to being captured by the cake [ 79 ]. An apparent decrease in the turbidity of permeate samples during the pressure driven separation processes of fermentation broths has also been reported in several previous studies [ 5 , 7 , 72 , 80 ].…”
Section: Resultssupporting
confidence: 82%
“…Membranes 2021, 11, x FOR PEER REVIEW 10 of 27 as particles with diameters smaller than the pore size of the membrane are more susceptible to being captured by the cake [79]. An apparent decrease in the turbidity of permeate samples during the pressure driven separation processes of fermentation broths has also been reported in several previous studies [5,7,72,80]. Figure 6 shows the SEM image of the PP S6/2 membrane surface after the MF process of fermentation broth with Citrobacter freundii performed under TMP of 0.03 MPa and VF of 0.8 m/s.…”
Section: Filtration Of Fermentation Broths With Citrobacer Freundii Bacteriasupporting
confidence: 55%
See 2 more Smart Citations
“…Importantly, summarizing the literature data (Table A1) it can be indicated that NaOH has been used to clean both polymeric [25,41] and ceramic [28,42] UF membranes applied in MBR technology. Our previous investigations [84,85] highlighted the efficiency of NaOH solutions in removing foulants from ceramic UF membranes after filtration of glycerol postfermentation solutions containing 1,3-propanediol as a main product. An important point which should be noted is that the chemical cleaning process generates a waste of spent cleaning solutions which undoubtedly should be considered during the MBRs design stage.…”
Section: Introductionmentioning
confidence: 99%